Kepuasan Pelanggan dan Inovasi pada Coffee Shop di Jakarta - Hilmi Akbar Hibbani; Riorini, Sri Vandayuli; Kahfi, Zhavira (Business, Economics dan Entrepreneurship, 2024)
This study aims to examine the relationship between Customer Orientation, Customer Relationship Orientation, Firm Innovativeness, and Business Growth in five popular coffee shops in Jakarta. Data were collected through a survey of 120 regular customers of Toko Kopi Tuku, Kopie Soe, Kopi Nako, Kopi Lima Detik, and Kopi Nalar using questionnaires as the primary data collection tool. A quantitative approach was employed, supported by statistical analysis. The findings reveal that Customer Orientation and Customer Relationship Orientation significantly influence Firm Innovativeness, which subsequentl impacts Business Growth positively. Further analysis highlights that well-managed innovation acts as a catalyst for sustainable business growth. Strong customer relationships and a focus on customer needs also play a crucial role in driving innovation. This study offers strategic insights for coffee shop managers to enhance their competitiveness by adopting customer-centric and innovation-driven strategies. The research adhered to ethical principles, including participant consent and data anonymity. Data validity and reliability were tested using SPSS software, and hypothesis testing was conducted with Amos software.